The Maintainability of Acehnese by Its Speakers at the Eastern Coast of Serdang Bedagai - Hadi Sahputra; Busmin Gurning; Syahron Lubis (Universitas Negeri Medan, 2014)
This qualitative study is designed to find the Acehnese speakers’ attitude in maintaining Acehnese at the eastern coast of Serdang Bedagai Regency. The subjects are thirty intra-marriage Acehnese speakers living long time the districts. Questionnaire is used to find out their daily attitude in communicating and to gather the data about what language they use in the communications and interaction with their husband or wife, children, brothers and sisters, neighbors, and colleagues. Interview is used to find out the positive and negative attitude. These attitudes are influenced by some factors which are analyzed and can be maintained Acehnese at the eastern coast of Serdang Bedagai Regency, living in Acehnese multi-ethnics, use Acehnese in their family every day, and having pride of their own language, use Acehnese to their neighbors and their colleagues. Currently, the existence of Acehnese is the speakers of Acehnese are at the level of safe but in their children or their generation is at the level of unsafe and it leads to the language shift to a dominant language, that is, Indonesian language as well as Malay language and Javanese language or other local language which are the major population, which dominate the use of vernacular. This is due to the weaknesses of vernacular speakers or the loss of belonging to their own language. Key words: attitudes, language maintenance, language shift, maintainability, vernaculars